Fanerogams from Huancayo, Peru - Yarupaitán Galván, Genaro (2004)
A detailed list of 328 fanerogams species included in 61 families are presented. The list is including life forms, altitudinal ranges, and common names of species that have been reported in Huancayo province, Junin, Central Perú.